Working Through Ethics in Education and Leadership - Donlevy, J. Kent. author. aut Link
IX, 156 p.
Keywords: This book, although targeting educational leaders, - teachers, school-based administrators, superintendents, board members, policy makers and education students, is also addressed to those interested in the topic of ethics and those who seek the development of an ethical awareness and an appropriate intellectual processes when facing ethical issues. In particular, the book uses both deductive and inductive methods to provide the reader with a progressive experience of ethical discernment and analysis in order to deal with and prepare the reader to address ethical issues in the public square - a task which requires that such decisions are rational, defensible, and clearly articulated. Institutional leaders' diligence and integrity requires no less in attaining and sustaining the support of those they must lead in and through the institutional decisions and policies which effect constituents' lives. Through the use of clearly stated definitions, the presentation of ethical schools of thought, cases, original plays - within which readers are encouraged to engage while in a safe learning environment - and references to poems, movie, and video clips, the book provides a lively and challenging approach to studying the topic of ethics.